Differentials in Reproductive Health Knowledge among Adolescents in Indonesia - Sari Kistiana; Desy Nuri Fajarningtiyas; Syauqy Lukman (Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Due to societal taboos, traditional and religious norms, Indonesia’s Z-generation, who account for a large population, is frequently underinformed about reproductive health. The objectives of this study are to determine whether there are any differences in the knowledge of Indonesian young adults on reproductive health issues, modern contraceptive methods, and sources of information for reproductive health by selected sociodemographic characteristics. From the 2019 Performance and Accountability Survey, 41.582 never-married adolescents between the ages of 10 to 24 years were selected for the analysis. In this study, descriptive and bivariate analyses were performed. The means of the two groups were compared using t-tests. The results show that adolescents still lack information about reproductive health. The overall means for knowledge of reproductive health, modern methods of contraception, and sources of information about reproductive health were 1.97, 2.54, and 3.07, respectively. Adolescents were highly exposed to message about reproductive health on television and the internet. Adolescents that are older, reside in urban areas, are more educated, and are wealthier are reported to have significantly higher knowledge than their counterparts. With enough concern and increased attention being provided to younger adolescents, who reside in rural areas, who have lesser education, and are from the lowest wealth index, emphasis should be placed on increasing information to promote reproductive health literacy among adolescents. Television and digital media are crucial communication channels for educating with young people about reproductive health. Policies and programs should be designed to involve peers, relatives, and teachers in providing information about reproductive health.